Costa rican drinking-water quality and availability index - Mora-Alvarado, Darner Adrián (2019)
The present document aims to create a composite indicator for assessing drinking-water quality and availability based on continuity intervals for water supply and the drinking-water quality risks index (ircach) developed by the laboratorio nacional de aguas (lna). The methodology consisted of the followings: 1) defining the intervals of the ircach, 2) proposing continuity intervals for water supply measured in hours and percentages, 3) defining the drinking-water quality and availability index (iccsach), and 4) applying the iccsach to ten aqueducts operated by aya. Results showed five categories for assessing water supply: excellent for 100 % of continuity, good for at least 80 % and less than 100 % of continuity, regular for at least 60 % and less than 80 % of continuity, bad for at least 40 % and less than 60 % of continuity, and very bad for less than 40 % of continuity. For the 2018 drinking-water assessment, the present document recommends applying the iccsach for the aya aqueducts only and included municipalities and rural aqueducts for the 2019 drinking-water assessment. Subsequently, it is recommended to include water volume to the index in order to assess water supply system.